Design, Control, and Testing of a Multifunctional Soft Robotic Gripper - Ana Correia; Tiago Charters; Afonso Leite; Francisco Campos; Nuno Monge; André Rocha; Mário J. G. C. Mendes (Actuators)
This paper proposes a multifunctional soft robotic gripper for a Dobot robot to handle sensitive products. The gripper is based on pneumatic network (PneuNet) bending actuators. In this study, two different models of PneuNet actuators have been studied, designed, simulated, experimentally tested, and validated using two different techniques (3D printing and molding) and three different materials: FilaFlex 60A (3D-printed), Elastosil M4601, and Dragonskin Fast 10 silicones (with molds). A new soft gripper design for the Dobot robot is presented, and a new design/production approach with molds is proposed to obtain the gripper’s PneuNet multifunctional actuators. It also describes a new control approach that is used to control the PneuNet actuators and gripper function, using compressed air generated by a small compressor/air pump, a pressure sensor, a mini valve, etc., and executing on a low-cost controller board—Arduino UNO. This paper presents the main simulation and experimental results of this research study.